Effects of Pinealectomy and Melatonin Application on Serum Melatonin, Nesfatin-1 and Ghrelin Levels - Sonmez, Saadet; Menevse, Esma; Baltaci, Saltuk Bugra; Unal, Omer; Mogulkoc, Rasim; Baltaci, Abdulkerim Kasim (European Journal of Therapeutics, 2023)
Objective: In this study, it was aimed to investigate the relationship between the pineal gland and ghrelin and nesfatin-1 hormones in rats. Methods: A total of 36 male rats were used in the study, and the animals were divided into 4 groups. Group 1, Control; Group 2, Pinealectomy (Px); Group 3, Px+Melatonin; Group 4 Melatonin. After the end of the experimental applications, melatonin, ghrelin and nesfatin-1 levels (ELISA) were determined in the blood samples taken from the animals. Results: While pinealectomy resulted in suppression of melatonin levels, melatonin supplementation led to a significant increase in blood melatonin levels (p<0.01). Melatonin supplementation suppressed ghrelin levels, while pinealectomy increased ghrelin levels (P<0.01). On the other hand, Nesfatin-1 levels, which increased with melatonin support, were significantly suppressed by pinealectomy (p<0.01). Conclusion: The results of the current study show that the pineal gland may have important effects on the hormones ghrelin and nesfatin-1, which play critical roles in nutrition. In conclusion melatonin supplementation inhibites ghrelin, and but increases nesfatin-1.